Analysis of credit risk on Islamic and Commercial banks in Malaysia / Suhaily Maizan Abdul Manaf, Yusnabilah Mohd Yusri and Fathiyah Ismail - Abdul Manaf, Suhaily Maizan; Mohd Yusri, Yusnabilah; Ismail, Fathiyah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
The financial market plays a major role to facilitate risk-sharing and efficient allocation of assets between investors. Credit-risk management is one of the essential activities banks must undertake to survive the ever-growing competition in the banking sector. Accordingly, credit-risk management is one of the most severe challenges or problems faced by the financial sector, mainly influenced by multiple factors that should not be overlooked. However, do credit risks have an impact on banks in Malaysia? The rationale of this study is to conduct an empirical analysis on the determinants of credit risk among the Islamic and conventional banks in Malaysia. There are six (6) determinants identified as independent variables in this study, namely return on assets (ROA), return on equities (ROE), banks' inefficiency (IE), loan-to-deposit ratio (LDR), inflation rate (IR), and exchange rate (ER), while credit risk (CR) as a dependent variable. Secondary data have been collected from the 16 Islamic banks and 26 commercial banks in Malaysia from 2009 until 2019 (11 years) by using Thomson Reuters Eikon. Using the regression analysis and Random Effect Model, findings reveal that all the independent variables have a positive, significant relationship towards credit-risk measurement, except for return on equities that has a significant, negative relationship with the dependent variable. It is finally concluded that future researchers should fill the gaps by investigating these variables in other countries to compare and give some suggestions on policymakers on credit-risk situations for such countries.